Thermal characterization in a circular tube fitted with inclined horseshoe baffles - Promvonge, Pongjet; Tamna, Sombat; Pimsarn, Monsak; Thianpong, Chinaruk (My University, 2015)
In the present study, the influence of inclined horseshoes baffles placed repeatedly in a tubular heat exchanger on heat transfer rate, friction factor and thermal enhancement factor are experimentally determined. The horseshoe baffle elements with an inclination angle of 20° were inserted periodically into the test tube at three different baffle-pitch ratios (PR = 0.5, 1.0 and 2) and -width or blockage ratios (BR = 0.1, 0.15 and 0.2). The experiment was conducted in the test tube having a uniform heat-fluxed wall by varying turbulent airflow to obtain Reynolds number in a range of 5300-24,000. The experimental results revealed that the tube fitted with inclined horseshoes baffles provides considerable improvement of the heat transfer rate over the plain tube around 92-208% while the friction factor is increased at about 1.76-6.37 times. To access the real benefits for the inclined horseshoes baffles inserted in plain tube, thermal performance factor is examined and found to be in the range of 1.34-1.92 at which the maximum obtained at PR = 0.5 and BR = 0.1 is considerably higher than that for published inserted devices. Correlations for Nusselt number and friction factor for the oblique horseshoe-baffled tube are also proposed.
Keywords: Friction factor; Heat transfer; Horseshoe-baffle; Thermal performance; Vortex generator